2021
DOI: 10.1186/s12884-021-03726-4
|View full text |Cite|
|
Sign up to set email alerts
|

A birth population-based survey of preterm morbidity and mortality by gestational age

Abstract: Background Despite 15–17 millions of annual births in China, there is a paucity of information on prevalence and outcome of preterm birth. We characterized the outcome of preterm births and hospitalized preterm infants by gestational age (GA) in Huai’an in 2015, an emerging prefectural region of China. Methods Of 59,245 regional total births, clinical data on 2651 preterm births and 1941 hospitalized preterm neonates were extracted from Huai’an Wom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…The need for in-hospital care was defined as admissions into any neonatal ward or NICU within neonatal period (0-27 postnatal days) for term births or within adjusted GA of preterm infants equivalent to 28 postnatal days for term births. All the above-mentioned perinatal and neonatal diagnoses or definitions were consistent with previous studies [ 11 15 ].…”
Section: Methodssupporting
confidence: 85%
See 2 more Smart Citations
“…The need for in-hospital care was defined as admissions into any neonatal ward or NICU within neonatal period (0-27 postnatal days) for term births or within adjusted GA of preterm infants equivalent to 28 postnatal days for term births. All the above-mentioned perinatal and neonatal diagnoses or definitions were consistent with previous studies [ 11 15 ].…”
Section: Methodssupporting
confidence: 85%
“…For those infant deaths without admission into, or after discharge from, any neonatal ward or NICU were classified as out-of-hospital deaths, which were derived from regional death report system (MCHSS) after verification of corresponding clinical records. By integrating the data of all infant deaths from the two sources, a new integrated database was established as a cohort linking information of livebirths, neonatal hospitalization and/or infant death for final analysis [ 15 ]. Works of retrospective data collection and analysis were conducted in 2018-2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm birth is the leading cause of neonatal morbidity and mortality worldwide [ 1 3 ], with two-thirds of all cases preceded by spontaneous preterm labor [ 4 ]. The latter is a syndrome comprising multiple etiologies [ 4 , 5 ], with intra-amniotic infection and/or inflammation as the only well-established causal link to preterm birth [ 6 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported an error in Table 4 heading (continued) in the PDF version is incorrect, “A. The total preterm births” should be “B.…”
mentioning
confidence: 99%